Diagnostic Potential of Distortion Product Otoacoustic Emissions in Noninvasive Assessment of Elevated Intracranial Pressure: Different Patterns of DPOAE Alterations in the Guinea Pig. (28th December 2011) - Strassen, Ulrich; Deppe, Christoph; Mees, Klaus; Plesnila, Nikolaus; Canis, Martin; Strieth, Sebastian; Olzowy, Bernhard
Abstract : Distortion product otoacoustic emissions (DPOAEs) have been proposed for monitoring the intracranial pressure (ICP) noninvasively. Aim of this study was to establish an animal model in the guinea pig for a detailed characterisation of ICP-related DPOAE alterations. In guinea pigs, the ICP was elevated experimentally and the DPOAE levels were continuously monitored. Two different patterns of DPOAE level changes were observed: (1) a decrease of few decibels affecting mainly the frequencyf 2 = 2 kHz with instant recovery after normalization of ICP, probably related to alterations of middle ear sound transmission; (2) a more pronounced level decrease affecting all frequencies, combined with a second decrease and prolonged recovery after ICP normalization, which might be related to alterations of the cochlear blood flow. Alterations of the levels of DPOAEs might not only provide information about ICP but also indicate critical ICP-induced reductions of the cochlear and the cerebral perfusion pressure.